WEhy bother?: Rethinking participation in elections and protests - Aytac, S. Erdem; Stokes, Susan C. (New York Cambridge University Press, 2019)
Why do vote-suppression efforts sometimes fail? Why does police repression of demonstrators sometimes turn localized protests into massive, national movements? How do politicians and activists manipulate people's emotions to get them involved? The authors of Why Bother? offer a new theory of why people take part in collective action in politics, and test it in the contexts of voting and protesting.